2016
DOI: 10.1002/jobm.201500775
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall composition plays a key role on sensitivity of filamentous fungi to chitosan

Abstract: Chitosan antifungal activity has been reported for both filamentous fungi and yeast. Previous studies have shown fungal plasma membrane as main chitosan target. However, the role of the fungal cell wall (CW) in their response to chitosan is unknown. We show that cell wall regeneration in Neurospora crassa (chitosan sensitive) protoplasts protects them from chitosan damage. Caspofungin, a β-1,3-glucan synthase inhibitor, showed a synergistic antifungal effect with chitosan for N. crassa but not for Pochonia chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Different studies have demonstrated that fungi membrane mainly containing polyunsaturated free fatty acids are sensitive to chitosan activity [58,64].…”
Section: Resultsmentioning
confidence: 99%
“…Different studies have demonstrated that fungi membrane mainly containing polyunsaturated free fatty acids are sensitive to chitosan activity [58,64].…”
Section: Resultsmentioning
confidence: 99%
“…Chitin, a cellulose-like polysaccharide linked by β 1-4 N -acetylglucosamine, is present in the exoskeleton of crab and shrimp [ 21 , 22 ]. Via chitinase digestion, chitin oligosaccharide ( N -acetyl-chitooligosaccharide, NACOS) can be produced and further deacetylated into chitosan oligosaccharide (COS) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chitin, a homopolysaccharide with the structure of N-acetylglucosamine polymerized by beta binding, is presented in the exoskeleton of crab and shrimp. 45,46 NACOS can be produced via chitinase digestion. NACOS with the polymerization degree 2-6 have shown therapeutic effects on multiple diseases such as cancer and gastritis.…”
Section: Biological Activities and Molecular Structures Of Oligosacchmentioning
confidence: 99%